Nutritional supplement use by Dutch elite and sub-elite athletes: Does receiving dietary counseling make a difference? - Wardenaar, F. C.; Ceelen, I. J. M.; van Dijk, J.-W.; Hangelbroek, R. W. J.; Van Roy, L.; Van der Pouw, B.; De Vries, J. H. M.; Mensink, M.; Witkamp, R. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
The use of nutritional supplements is highly prevalent among athletes. In this cross-sectional study, we assessed the prevalence of nutritional supplement use by a large group of Dutch competitive athletes in relation to dietary counseling. A total of 778 athletes (407 males and 371 females) completed a web-based questionnaire about the use of nutritional supplements. Log-binomial regression models were applied to estimate crude and adjusted prevalence ratios (PR) for the use of individual nutritional supplements in athletes receiving dietary counseling as compared with athletes not receiving dietary counseling. Of the athletes, 97.2% had used nutritional supplements at some time during their sports career, whereas 84.7% indicated having used supplements during the last 4 weeks. The top ranked supplements used over the last 4 weeks from dietary supplements, sport nutrition products and ergogenic supplements were multivitamin and mineral preparations (42.9%), isotonic sports drinks (44.1%) and caffeine (13.0%). After adjustment for elite status, age, and weekly exercise duration, dietary counseling was associated with a higher prevalence of the use of vitamin D, recovery drinks, energy bars, isotonic drinks with protein, dextrose, beta-alanine, and sodium bicarbonate. In contrast, dietary counseling was inversely associated with the use of combivitamins, calcium, vitamin E, vitamin B2, retinol, energy drinks and BCAA and other amino acids. In conclusion, almost all athletes had used nutritional supplements at some time during their athletic career. Receiving dietary counseling seemed to result in better-informed choices with respect to the use of nutritional supplements related to performance, recovery, and health.